KINERJA PEGAWAI BALAI BESAR PENDIDIKAN DAN PELATIHAN KESEJAHTERAAN SOSIAL (BBPPKS) REGIONAL IV KALIMANTAN - Rizki Putri Amelia; Achmad Alim Bachri; Jamaluddin Jamaluddin (Jurnal Manajemen Dayasaing, 2019)
The purpose of this research is: 1. To know performance employees at of big hall education and training social welfare (BBPPKS) regional IV of Kalimantan. 2. To know problems of performance often occurs in big hall education and training social welfare (BBPPKS) regional IV of Kalimantan. This study used a descriptive research design with qualitative approach. Data collection techniques used through interviews, observation and documentation. Informants were taken from origin policy makers and stakeholders. Analysis using interactive data analysis which consists of data reduction, data presentation and conclusion. The results show that the employee performance research big hall education and training social welfare (BBPPKS) regional IV of Kalimantan seen the purpose the employee performance, the employee performance standards and motives have not reached the level the employee performance levels while the accountability the employee performance has begun to reach this optimal. The distribution of work in education and training of big hall social welfare (BBPPKS) regional IV of Kalimantan formally have refer to the regulations concerning the formulation of the, however sometimes the allocation of work to personnel less consistent with his position. Here it can be seen that responsibility the performance of on officer at of big hall for training and education of people with social welfare (BBPPKS) regional IV of Kalimantan as part of the has not yet been it is said the implementation of the activity aligned with the government of a prescribed procedure.